2020
DOI: 10.1002/adma.202006087
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N,N′‐bis‐4‐butylphenyl‐N,N′‐bisphenyl)benzidine‐Based Interfacial Passivation Strategy Promoting Efficiency and Operational Stability of Perovskite Solar Cells in Regular Architecture

Abstract: The failure of perovskite solar cells (PSCs) to maintain their maximum efficiency over a prolonged time is due to the deterioration of the light harvesting material under environmental factors such as humidity, heat, and light. Systematically elucidating and eliminating such degradation pathways are critical to imminent commercial use of this technology. Here, a straightforward approach is introduced to reduce the level of defect‐states present at the perovskite and hole transporting layer interface by treatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 56 publications
1
114
0
1
Order By: Relevance
“…Reproduced with permission. [278] Copyright 2020, Wiley-VCH. www.advancedsciencenews.com various perovskite systems must therefore be performed, as a universal crystallization modulating strategy is highly desirable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [278] Copyright 2020, Wiley-VCH. www.advancedsciencenews.com various perovskite systems must therefore be performed, as a universal crystallization modulating strategy is highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Akman et al recently reported that poly(N,N′-bis-4butylphenyl-N,N′-bisphenyl)benzidine (poly-TPD) has a strong passivation effect on perovskites. [278] They found that top-coated poly-TPD reacted with Pb defects and thus improved the surface morphology of perovskite films (Figure 24e,f), and that the hydrophobicity of poly-TPD led to substantially enhanced device stability under an ambient atmosphere.…”
Section: Top-layer Modification Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9–12 ] Moreover, numerous effective strategies have been reported to passivate the surface defects of top region of perovskite interconnecting with the carrier transport layer (CTL), and thus to enhance the stability and performance of PSCs. [ 6,13,14 ] Meanwhile, the bottom interface also plays a critical role in the degradation of perovskite active layer and PSC performance and stability. [ 15–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Another polymeric HTL material, namely, poly‐TPD, displays similar energy levels, intrinsic hole mobility, and thermal stability versus PTAA. [ 26–28 ] Nonetheless, an obvious gap in the device performance still exists between poly‐TPD and PTAA‐based IPSCs (21.3% vs 22.7%). [ 29 ] This is because the intrinsic nonwetting property of poly‐TPD makes the perovskite precursor solution difficult to spread out and coat the poly‐TPD surface, giving rise to more serious interfacial contact and recombination losses.…”
Section: Introductionmentioning
confidence: 99%